ANALISIS PENGUKURAN KINERJA PT X DENGAN PENDEKATAN BALANCE SCORE CARD - Sibarni, Bintang Berliana (JURNAL BISNIS & AKUNTANSI UNSURYA, 2020)
The Balanced Score Card method is used to measure company X's performance in terms of four perspectives; financial, customer, business operational, learning and growth. Primary data are used for customer perspectives, operational and business, learning and growth. Whereas the financial perspective uses secondary data; audited financial statements. The presentation technique uses descriptive analysis, the data collected is processed and analyzed quantitatively through answer by Likert scale. A bit for the financial perspective through financial ratios. The results showed that company performance differed for each perspective.Keywords: Balanced Score Card, financial, customer, business operational, learning and growth perspective